Acute hepatitis B virus infection in humanized chimeric mice has multiphasic viral kinetics. Issue 2 (6th June 2018) - Ishida, Yuji; Chung, Tje Lin; Imamura, Michio; Hiraga, Nobuhiko; Sen, Suranjana; Yokomichi, Hiroshi; Tateno, Chise; Canini, Laetitia; Perelson, Alan S.; Uprichard, Susan L.; Dahari, Harel; Chayama, Kazuaki
Abstract : Chimeric urokinase type plasminogen activator (uPA)/severely severe combined immunodeficiency (SCID) mice reconstituted with humanized livers are useful for studying hepatitis B virus (HBV) infection in the absence of an adaptive immune response. However, the detailed characterization of HBV infection kinetics necessary to enable in‐depth mechanistic studies in this in vivo HBV infection model is lacking. To characterize HBV kinetics post‐inoculation (p.i.) to steady state, 42 mice were inoculated with HBV. Serum HBV DNA was frequently measured from 1 minute to 63 days p.i. Total intrahepatic HBV DNA, HBV covalently closed circular DNA (cccDNA), and HBV RNA was measured in a subset of mice at 2, 4, 6, 10, and 13 weeks p.i. HBV half‐life (t1/2 ) was estimated using a linear mixed‐effects model. During the first 6 hours p.i., serum HBV declined in repopulated uPA/SCID mice with a t1/2 = 62 minutes (95% confidence interval [CI] = 59‐67). Thereafter, viral decline slowed followed by a 2‐day lower plateau. Subsequent viral amplification was multiphasic with an initial mean doubling time of t2 = 8 ± 3 hours followed by an interim plateau before prolonged amplification (t2 = 2 ± 0.5 days) to a final HBV steady state of 9.3 ± 0.3 log copies (cps)/mL. Serum HBV and intrahepatic HBV DNA were positively correlated (R 2 = 0.98). Conclusion: HBV infection in uPA/SCID chimeric mice is highly dynamic despite the absence of an adaptive immune response. Serum HBV t1/2 in humanized uPA/SCID mice was estimated to be ∼1 hour regardless of inoculum size. The HBV acute infection kinetics presented here is an important step in characterizing this experimental model system so that it can be effectively used to elucidate the dynamics of the HBV life cycle and thus possibly reveal effective antiviral drug targets. (Hepatology 2018).